Peran Teknologi Dalam Pelatihan Dan Pengembangan Sumber Daya Manusia Di Era Digital - Reski, Astria Utami Sri; Artisyah, Nurul Fitri; Eliyanti Agus Mokodompit, Muh Ashadi, (STIE AMKOP, 2025)
The rapid development of technology has brought significant changes in the way organizations conduct training and human resource development. Technology is now a key component in employee training, enabling more efficient and flexible methods, such as the use of e-learning, learning management systems (LMS), artificial intelligence and virtual-based simulations. This article aims to examine the role of technology in improving the effectiveness of HR development, as well as the challenges and barriers that organizations face in its implementation. Based on a comprehensive literature review, this article also explores the opportunities that arise in the digital era to build dynamic and competitive HR. The results show that technology provides easy access to learning, enables personalization of materials, and strengthens the work environment based on continuous learning. However, the successful implementation of technology is also strongly influenced by the readiness of infrastructure, organizational culture, and digital skills. Therefore, a training strategy is needed to have a long-term impact on improving organizational performance and competitiveness. This article presents a conceptual foundation and practical implications that can serve as a reference for practitioners and researchers in developing relevant training models in the digital era. Keywords: Techonlogy, training, HR development, digitalization, e-learning